2014
DOI: 10.1002/atr.1273
|View full text |Cite
|
Sign up to set email alerts
|

Whether to enter expressway or not? The impact of new variable message sign information

Abstract: SUMMARYThis study develops a random effect panel data logit model that identifies the factors that influence expressway users' decision behavior under a new arterial road variable message sign information service. The new information service provides travel time of both an expressway route and an alternate arterial road route. It is based on the data collected from a stated preference survey of Shanghai drivers. Correlations within repeated choices by the same respondent were addressed. The results show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Thus, with the release of information, to obtain the coordinate changes and the law of transition of the traffic flow state in road sections within the regional road network accurately is an important precondition for the state estimation of urban road traffic networks. Besides, a traffic administrator can assess the disturbance of such traffic information on the state of the road network, so as to develop traffic guidance strategies that are more reasonable; meanwhile e, it also helps to obtain 2 more accurate predictive values of the traffic flow state, so as to develop road traffic control strategies that are more practical [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with the release of information, to obtain the coordinate changes and the law of transition of the traffic flow state in road sections within the regional road network accurately is an important precondition for the state estimation of urban road traffic networks. Besides, a traffic administrator can assess the disturbance of such traffic information on the state of the road network, so as to develop traffic guidance strategies that are more reasonable; meanwhile e, it also helps to obtain 2 more accurate predictive values of the traffic flow state, so as to develop road traffic control strategies that are more practical [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a stated preference survey in China, Gan and Ye (2013) found that those who are not sensitive toward travel time savings do not have any intention to detour and do not actually detour. Thus, in a follow-up study, respondents stated that the detour likelihood increased with the increase in travel time savings on the alternate route (Gan and Ye, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A few studies have explored the effect of vehicle category on driver diversion, with passenger car drivers and professional drivers being considered. Ma et al [46] noted that taxi drivers exhibited lower diversion propensity compared to passenger car drivers, while Gan and Ye [47] did not find differences considering the diversion behaviour of these two populations. Peeta et al [48] noted different diversion behaviour between passenger cars and HGVs.…”
Section: Introductionmentioning
confidence: 99%